Consumer Legal Certainty in Grab Indonesia's Challenge Jugglenaut Program: An Analysis of the Abuse of Circumstances in Digital Contracts - Nayra Ambardani; Amoury Adi Sudiro; Siti Farhani (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The many reports from users about the Challenge Jugglenaut program by Grab Indonesia that do not provide rewards as promised show that there are problems in application-based online transportation services in Indonesia. The rapid advancement of digital technology has led to the birth of platforms such as Grab with lucrative promotional offers, but abusive practices that harm consumers are still common. This study aims to analyze the legal certainty of consumers for the delay in rewarding PT Grab Indonesia in the implementation of the Challenge Jugglenaut program by examining indications of abuse based on user experience. The research uses an empirical legal approach with qualitative methods and descriptive techniques to describe the real user experience. Data was collected through structured questionnaires, document studies, and literature references, then analyzed qualitatively to find patterns of abuse of circumstances and legal responsibilities of PT Grab Indonesia. The results of the analysis show that in the implementation of the Challenge Jugglenaut Program, there is an imbalance in the legal position between business actors and users, which is reflected in the disproportionate setting of targets and legal uncertainty in the requirements and mechanisms of the program. This condition shows that the contractual relationship built by the platform does not provide a clear and predictable guarantee regarding the fulfillment of consumer rights, thus weakening the principle of legal certainty in practice. Although normative consumer protection regulations are available, the findings of this study show that supervision and special regulation of digital platforms still need to be strengthened, especially related to the obligation of transparency of systems, algorithms, and program success assessment mechanisms. Therefore, cooperation between the government, business actors, and consumer protection institutions is needed to build a digital economy ecosystem that not only encourages innovation, but also ensures legal certainty, justice, and real protection of consumer rights.